Studies on Schismatoglottideae of Borneo XVI - Multinervia Complex - Wong, Sin Yeng; Boyce, P.C (The Japanese Society for Plant Systematics, 2011)
Schismatoglottis hayi S.Y. Wong & P.C. Boyce is described as a new species endemic to forested limestone outcrops at Niah National Park, NE Sarawak. It is morphologically most similar to S. multinervia M. Hotta, a species here redefined as being endemic to Mulu N.P., where it is obligated to limestone. Together these two species are proposed as constituting a new informal taxon, the Multinervia Complex, defined by the combination of vegetative tissues aromatic (terpenoids) when crushed, a fully adnate petiolar sheath, petioles and major veins abaxially pubescent, spathe limb darkening internally rapidly at onset of anthesis and thence splitting longitudinally into wide recurving strips, an hourglass-shaped spadix, and large staminodes in 1-2 rows at the junction of the pistillate zone with the spathe. Schismatoglottis hayi is, by modification to the existing key, included into a key to Bornean Schismatoglottis. Both species are illustrated. Previous confusion between S. hayi and S. puberulipes Alderw. is highlighted and clarified.